ASSOCIATION BETWEEN CLINICAL AND RADIOGRAPHIC CHARACTERISTICS OF MANDIBULAR THIRD MOLARS AND DISTAL CARIES IN ADJACENT SECOND MOLARS (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the association between clinical and radiographic characteristics of mandibular third molars and the prevalence of distal caries in the adjacent second molars.Subjects and methods: A cross-sectional study was conducted on 475 patients aged 18 and older at the Department of Oral Surgery, Ho Chi Minh city Odonto-Maxillo-Facial Hospital from July 2025 to December 2025. General information was collected via patient history interviews. Distal caries status and third molar characteristics were recorded through clinical examinations combined with digital panoramic radiograph analysis. Logistic regression analysis was employed with a significance level of p < 0.05.Results: The prevalence of distal caries in mandibular second molars was 49.5% among participants and 33.6% among total teeth examined. Logistic regression revealed that patients aged 25 and older and males had significantly higher risks, with odds ratios (OR) of 2.82 and 2.17, respectively (p < 0.001). Regarding third molar characteristics, partial eruption increased the risk of adjacent caries by 3.88 times compared to the clinically unerupted group. Mesioangular impaction was identified as the strongest risk factor (adjusted OR = 4.37; p < 0.001), followed by horizontal impaction (adjusted OR = 2.74; p = 0.002), both compared to vertical impaction.Conclusion: The prevalence of distal caries in mandibular second molars is high and closely associated with the eruption status and angulation of adjacent third molars, as well as demographic factors such as age and gender.
Keywords: Distal caries, mandibular second molar, third molar, panoramic radiograph.